Strong perpendicular magnetic anisotropy of Pt/Co/AlN structure - Won, Young Chan; Ahn, Jae-Pyoung; Lim, Sang Ho (Elsevier BV, 2022)
In this study, the perpendicular magnetic anisotropy (PMA) and microstructure of Pt/Co/AlN stacks were investigated. At a Co thickness of 0.5 nm, the magnetic moment was not observed in the as-deposited state, but after annealing, it increased significantly. Furthermore, a strong PMA was obtained in the annealed samples; after annealing at 300 degrees C and 400 degrees C, the effective PMA energy densities were 2.28 and 1.96 x 10(7) erg/cm(3), respectively. Similar behavior was observed for samples with thicker Co layers. The magnetic dead layer and interfacial PMA energy density were also investigated to determine the interfacial effects on PMA. The occurrence of strong PMA was supported by high-resolution cross-sectional transmission electron microscopy results, demonstrating a well-defined layered structure for the annealed Pt/Co/AlN samples. (C) 2022 Published by Elsevier B.V.